The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/mds.870120637
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic adverse reactions to intramuscular botulinum toxin type a injection

Abstract: Three cases of adverse reactions to repeated intramuscular botulinum toxin A (BTA) injections are described: a persistent rash on the face at the site of injection, a localized anaphylactic reaction following BTA injection into one leg, and bilateral ptosis repeatedly following BTA injection into neck muscles. The mechanisms for these idiosyncratic adverse responses are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Most reported adverse effects are benign and reversible, including injection site reactions [2], focal weakness [2] such as dysphagia, ptosis and strabismus, and subclinical effects on neuromuscular junctions of distant non-injected muscles [3]. Rare but potentially dangerous complications have also been described, including systemic botulism [4] and anaphylactic reactions [5], and cases of distant nerve injury have also been reported.…”
mentioning
confidence: 99%
“…Most reported adverse effects are benign and reversible, including injection site reactions [2], focal weakness [2] such as dysphagia, ptosis and strabismus, and subclinical effects on neuromuscular junctions of distant non-injected muscles [3]. Rare but potentially dangerous complications have also been described, including systemic botulism [4] and anaphylactic reactions [5], and cases of distant nerve injury have also been reported.…”
mentioning
confidence: 99%
“…34 Untoward outcomes of toxin injection also include idiosyncratic reaction-rash, swelling-or those resulting from a direct effect of the toxin-excessive dose, incorrect delivery, and unwanted spread to adjacent tissues. 17 Since the preparations for injection do not consist purely of botulinum A toxin, some of these idiosyncratic reactions could be related to other proteins. In an unusual episode of gastroesophageal reflux, confirmed by biopsy and 24-hr pH monitoring, esophageal ulceration, hemorrhage, and extraluminal esophageal inflammation was attributed to the botulinum A toxin injection; whether it was secondary to an immunologic reaction or local irritation is unknown.…”
Section: B O T U L I N U M T O X I Nmentioning
confidence: 99%
“…16 Due to a lack of standardized parameters for the performance of pneumatic dilation, the effect of inflation pressure and duration of inflation on the incidence of complications is not known. 17 While Eckardt et al 18 found that a balloon pressure higher than 7 psi was associated with higher rate of complications but not with a better outcome, others 8 have established a threshold of 11 psi. A recent study suggested that just the obliteration of the "waist" (constriction) produced by the sphincteric impression on the inflated bag is enough to achieve effective dilation, with no significant differences 28.3 ± 0.8…”
mentioning
confidence: 98%
“…Skin rash, edema, pruritus, local discoloration, psoriasiform eruption, and anaphylactoid reactions have been described previously, and some of them have occurred apart from the site of injection. [1][2][3][4] Generalized skin eruption typical of the drug allergy, however, has never been clearly documented in a medical journal, although it is mentioned by the manufacturer. 1,2 Allergic reactions can potentially occur due to the toxin protein itself, but as another explanation, the human serum albumin added to the toxin vial might be a cause, 5 and potentially contribute to more serious phenomena such as anaphylaxis.…”
Section: Botulinum Toxin and Skin Rash Reactionmentioning
confidence: 99%